Analisis Produktivitas dan Biaya Operasional Alat Berat pada Pekerjaan Ereksi Rangka Utama Jembatan Bagor - Ahmad Laudza Suari; Jovanda Rivansyah; Himatul Farichah (Jurnal Konstruksi, 2025)
This research aims to analyze heavy equipment productivity and estimate operational costs in the Bagor bridge replacement project. The methodology used includes collecting primary data through field observations to measure effective working hours and efficiency of heavy equipment, as well as secondary data which includes equipment specifications, number of tools, operational costs and work volume from related documents. The three types of heavy equipment analyzed are the Zaxis 200 Excavator, Zaxis 210 Excavator, Bomag BW 177 D-5 Vibro Roller, and Mitsubishi Fuso 6X4 Truck Trailer. The analysis results show that the productivity of each heavy equipment per day is 717.12 m³ for the Zaxis 200, 806.76 m³ for the Zaxis 210, 252.48 m³ for the Vibro Roller, and 149.99 m³ for the Truck Trailer. Total operational costs per day for all heavy equipment reach IDR 28,163,000. It is hoped that this research can provide recommendations for increasing the productivity of heavy equipment in bridge construction projects, so that projects can be completed more efficiently and effectively.